Romance Sebagai Media Pemunculan Gaya Pacaran Remaja Dalam Kacamata Islam - Sumarno Sumarno; Didin Nurul Rosidin (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
This research is motivated by the courtship style of today's teenagers who imitate the love story of teenagers in novel literary works. Many teenagers are in courtship relationships, even though Islam itself has regulated that dating relationships are prohibited. The purpose of this study is to find out whether romantis genre novels have a major influence on the emergence of adolescent courtship styles today. The research method used is a descriptive method with a mixed or combination approach (mixed methods).  Respondents in this study were adolescents who were in the age range of 15-23 years with a sample of 40 people. This study used a non-probability sampling technique, namely accidental sampling.  Based on the research that has been carried out, results were obtained in the form of: (1) The novels favoured by teenagers are romance novels; (2) There is dating behaviour in the novel that is inconsistent with Islamic law; (3) Romantic novels have a major influence on the emergence of teenage dating styles; (4) Courtship has become commonplace and natural today. Thus, it can be concluded that many teenagers know the law of dating in Islam, but still do so due to influencering factors, one of which is from the novel. So, teenagers should also read Islamic romantic novels that revolve around love in Islamic teachings.